Crystal Structure of (NH4)9(P2VW44O78)(H2O)2 - Liu, Hai-Xing; Ren, Xiao-Yan; Wan, Li-Mei; Zhang, Yun-Chen; Tai, Xi-Shi (Asian Journal of Chemistry, 2012)
The title compound, (NH4)9(P2VW22O78)(H2O)2, is prepared by hydrothermal method. It contains PVW heteropolyacid anion, ammonium cations and water molecular. The crystal packing is stabilized by intermolecular N-H···O and N-H···N hydrogen bonds interaction.